1994
DOI: 10.1007/bf01275530
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of membrane glycoprotein in amoeboid microglia transforming into ramified microglia in postnatal rat brain

Abstract: The present study describes the ultrastructural localization and labelling pattern of lectin in different microglial cell phenotypes in the postnatal rat brain using the isolectin, GSA I-B4. The nascent round and amoeboid microglial cells (round cells and cells displaying short processes) were labelled at their cytoplasmic membrane and the membrane of the subplasmalemmal vacuoles. In the course of their transformation into ramified forms with age, dense lectin labelling was observed successively at different s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 33 publications
1
16
1
Order By: Relevance
“…After P28, in the double staining examination, it was difficult to detect microglial cells with IB4 immunohistochemistry because of its reduced intensity, in accordance with the findings of Wu et al [38], while the same cell showed strong immunostaining with anti-Tb4 antibody. To the contrary, blood vessels were always strongly IB4 positive in any age group.…”
Section: Tb4 Positive Cells and Microgliasupporting
confidence: 68%
See 1 more Smart Citation
“…After P28, in the double staining examination, it was difficult to detect microglial cells with IB4 immunohistochemistry because of its reduced intensity, in accordance with the findings of Wu et al [38], while the same cell showed strong immunostaining with anti-Tb4 antibody. To the contrary, blood vessels were always strongly IB4 positive in any age group.…”
Section: Tb4 Positive Cells and Microgliasupporting
confidence: 68%
“…However, Tb4 immunoreactive cells have not been well investigated in the developing rat brain. On the other hand, IB4 is known as a common marker for microglia [22,34], although it has been pointed out that detection of microglial cells with IB4 becomes gradually difficult with their maturation [38]. We studied Tb4 immu- nohistochemistry of cortical cells in comparison with IB4 in developing rat brain.…”
Section: Tb4 Positive Cells and Microgliamentioning
confidence: 99%
“…Labeling with GSA I-B 4 is widely accepted to stain microglial cells at both light and electron microscopic levels (e.g., Streit and Kreutzberg, 1987;Marty et al, 1991;Riva-Depaty et al, 1994;Wu et al, 1994). However, the stainability of microglial cells strongly depends on their activation.…”
Section: Gsa I-b 4 Histochemistry Labels Activated Microglial Cellsmentioning
confidence: 99%
“…An immunocytochemical study by Wu et al (1994) described gradual modi®cations (downregulation) in the membrane glycoprotein(s) recognized by the isolectin B 4 of Bandeiraea simplicifolia during transformation of ameboid microglia into rami®ed microglia. The labeling of rami®ed microglia with this lectin was weaker than that of brain macrophages.…”
Section: Differentiation Of Microglial Cellsmentioning
confidence: 99%